Analysis of Custodial Deaths in New Delhi: A 13 Years Study - Jhamad, Akhilesh R; Sikary, Asit Kumar; Millo , T (Journal of Indian Academy of Forensic Medicine, 2014)
Custody related deaths are not uncommon in India. A meticulous autopsy becomes a necessary  part of the investigation. A retrospective study was done to analyze the prevalence and demographic  pattern of custodial related deaths, whose autopsy were conducted at AIIMS, New Delhi. The autopsy  reports of 13 years (1999-2011) were analyzed retrospectively. There were total 15 cases of custodial  related deaths. All cases were male and majority was in the age group of 25-35 years (8 cases). 9 cases  belonged to Hindu and 6 cases belong to Muslim. 10 cases died due to natural disease and 3 cases due  to unnatural causes. 10 cases died in the hospital and 5 cases in the custody. Among the 3 unnatural  deaths 1 died due to hanging, 1 due to fall from height and 1 from blunt injuries. In 2 cases no exact  cause of death could be determined. In India there is overcrowding of prisoners in the jail. In spite of  medical screening of the prisoners the infectious diseases like TB is very prevalent in jails. The national  human rights commission is taking up the issues to improve the jail conditions in India.
Keywords: Custody; Custodial deaths; Suicide; Human rights